2019
DOI: 10.3389/fpubh.2019.00051
|View full text |Cite
|
Sign up to set email alerts
|

Even a Previous Light-Active Physical Activity at Work Still Reduces Late Myocardial Infarction and Stroke in Retired Adults Aged>65 Years by 32%: The PROOF Cohort Study

Abstract: Background: Work may contribute significantly to daily physical activity (PA) and sedentary behavior (SB). Physical inactivity and SB at work might be two major risk factors for premature morbidity. Therefore, the aim of this research was to describe self-reported past PA and SB at work and during leisure time within the PROOF cohort subjects, and to determine consequences of PA and SB on late health of these now retired workers.Material and Methods: The PROOF cohort study was used to prospectively allow asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
(50 reference statements)
1
8
0
Order By: Relevance
“…Several previous studies have supported our results [12,41,42]. In contrast, some results in previous studies found that LPA could produce health benefits [43]. For one thing, our study did not further divide physical into occupational and leisure-time PA. For another, we do not further divide LPA into a more detailed intensity of PA.…”
Section: Discussionsupporting
confidence: 81%
“…Several previous studies have supported our results [12,41,42]. In contrast, some results in previous studies found that LPA could produce health benefits [43]. For one thing, our study did not further divide physical into occupational and leisure-time PA. For another, we do not further divide LPA into a more detailed intensity of PA.…”
Section: Discussionsupporting
confidence: 81%
“…The preference to not perform moderate and vigorous physical activities have been widely reported in patients with PAD and has been attributed to the anticipation of claudication pain. Interestingly, in the elderly population, light-intensity physical activities have been associated with improvements in several health outcomes 17,18 , and the potential health benefits in PAD patients must be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This practice is important because its health benefits are well established (1). A recent study found a positive impact of PA on myocardial infarction and stroke in adults aged more than 65 years (2). Physical activity is a non-drug prevention solution (3,4).…”
Section: Introductionmentioning
confidence: 99%